The analysis of stationary condition of heat exchange processes in disperse layer - Mizernyi, V. M.; Modebadze, T. A. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The present paper considers the correctness of mathematic models of stationary conditions of ironstone pellet roasting on the uninterrupted conveyer machine on the basis of non linear heat exchange process analysis in two-phase environments